Rainforest research journal - Mason, Paul, 1967- (St. Catharines, Ont. ; New York : Crabtree Pub., 2011)
Provides information about rain forests in the form of a research journal, including facts about rivers, animals, Yanomami Indians, plants, and more.
Resource Links, April 2011
Includes bibliographical references (p. 31) and index.
5.4
3-6
Keywords: Rain forest ecology -- Research -- Diaries -- Juvenile literature; Rain forest ecology -- Amazon River Region -- Juvenile literature; Rain forest ecology; Amazon River Region